What are the main factors driving behind the MENA countries current account deficit? A panel logit approach analysis - Mohammed Seghir Guellil; Salah Eddine Sari Hassoun; Jorge Chica-Olmo; Mehmet Saraç (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
The sustained current account deficit in any country has an important implication for policy. If it continues, then it suggests that the regime ought to have no motivation to avoid or to diminish its international debt. In this paper, we test empirically the relationship among current account deficit and different macroeconomic variables by using panel Logit model. Therefore, we focus on the MENA countries during the years of 1980-2017. We built an econometric model to analyse the contribution of the real GDP, unemployment rate (UR), consumer price index (CPI), export growth rate (EGR), import growth rate (IGR), public expenditures (PE), and foreign trade rate (FTR) on current account deficit (CAD). We established that only the following exogenous variables: GDP, UR, PE and FTR have a positive and significant effect on the current account deficit. This outcome may support governments to identify the best time for investment and business strategies by observing the evolution of the performance of higher temporal hierarchy industries.
Keywords: C13; C23; C51; C52; C55; C58; G17; G18; G28; 330; current account deficit; panel Logit model; MENA countries; macroeconomic variables